2015
DOI: 10.1590/0104-6632.20150322s00003667
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Estrogens by Activated Sludge Under Different Conditions Using Batch Experiments

Abstract: -Wastewater treatment by deactivated and activated sludge was investigated to evaluate the removal of estrogens [estrone (E1), 17β-estradiol (E2), 17α-ethinylestradiol (EE2)] via adsorption and degradation. Different treatment conditions were used, including three mixed liquor volatile suspended solid (MLVSS) concentrations, three methanol concentrations (carbon source) and three types of aqueous media (water, synthetic solution, and supernatant). The E2 was degraded the fastest by the bacterial community. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…In addition, certain secondary treatment solutions have wide quiescent surfaces, including sequencing batch reactors during the settle and decant phases as well as biological aerated ilters awaiting backwash. All of these can be considerable sources of odor emissions in the atmosphere [33]. Regarding table 3, it can be shown that the phases of equalization and Primary Clari ier produce the most gaseous contaminants in all the treatment levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, certain secondary treatment solutions have wide quiescent surfaces, including sequencing batch reactors during the settle and decant phases as well as biological aerated ilters awaiting backwash. All of these can be considerable sources of odor emissions in the atmosphere [33]. Regarding table 3, it can be shown that the phases of equalization and Primary Clari ier produce the most gaseous contaminants in all the treatment levels.…”
Section: Resultsmentioning
confidence: 99%
“…Two main assumptions were used in constructing formulations for these transfer processes: Henry's law and the two-ilm resistance theory apply. The process of transferring a compound from an area source, such as a primary tank surface and the surface of diffused aerated activated sludge reactor, to the atmosphere is known as volatilization [25,33]. Because the overall mass transfer coef icient plays such a signi icant role in determining volatilization rates, it must be accurately analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The chemicals were added to test vessels in a solution of methanol or acetone-volume of solvent added was limited to 0.1% to minimize any potential effect. These solvents will not inhibit microbial action as methanol is non-toxic to microorganisms below 1,000 mg/L (Novak et al, 1985;Brasil Bernardelli et al, 2015) and acetone is non-toxic below 5% v/v in different redox conditions (González, 2006). For the aerobic experiment, 1,000 μg/L for triclosan, 200 μg/L for PAHs, 100 μg/L for estrogens and 30 μg/L for PBDEs were spiked into the test vessels.…”
Section: Experimental Design Of Biodegradation Assaymentioning
confidence: 99%
“…Moreover, it was shown that the degradation rate depended on the carbon to nitrogen ratio - the lower it was, the faster the estrogen decomposition was. In addition, 17β-estradiol is usually degraded faster while estrone and synthetic estrogens are decomposed slower [ 34 , 47 ]. Moreover, Wang et al [ 37 ] noted the synergistic effect of mixture strains during 17β-estradiol degradation.…”
Section: Microbiological Degradation Of Edcsmentioning
confidence: 99%